(untitled) (Research, Society and Development, 2020)
The present study aimed to develop edible popsicles sticks, with the goal replacing the sticks, currently made of wood or plastic, for a biscuit that can be eaten together with the ice cream. Thereunto, three biscuit formulations were developed (F1, F2 e F3). The formulation F3, was prepared with wheat flour and used as a basis for the development of other formulations, whereupon wheat flour was replaced by oat and rice flour (F2) and by different sources of starch (polished rice, corn and manioc) (F3), in addition to other modifications. Physical-chemical evaluations were carried out (water activity, moisture, texture, specific volume and expansion).In the texture analysis, the three formulations showed no significant difference(p>0,05).The formulations F1 and F3 had the lowest values ​​for water activity and moisture, respectively(p<0,05).In relation to the specific volume, the formulation F3 presented the same volume as F2 (p> 0.05) which, in turn, was equal to the volume of the F1 (p> 0.05). As for expansion, formulation F2 showed greater expansion than formulation F1, however both presented the same expansion as formulation F3 (p> 0.05).). Lastly, it was observed that the three formulations fit the study proposal. The biscuits presented characteristics expected for this type of product, in addition to having enough strength to sustain a popsicle. However, the F1 formulation was the one with the best potential for this purpose in the current market, as it is also related to the trend towards healthiness.